Identification of deleterious variants of uncertain significance in BRCA2 BRC4 repeat through molecular dynamics simulations. (22nd March 2022) - Sinha, Siddharth; Qin, Zixin; Tam, Benjamin; Wang, San Ming
Abstract: Large quantity of variants of uncertain significance (VUS) has been identified in cancer predisposition genes, but classification of VUS remains a big challenge. We proposed that the impact of VUS on protein structure stability can be used to identify these with deleterious effects by using molecular dynamics simulation (MDS)-based approach and developed a MDS-based method for missense VUS classification. In the current study, we applied the system to classify the missense VUS in BRCA2. BRCA2 plays an important role in maintaining genome stability by repairing double-strand DNA damage through homologous recombination. BRCA2 BRC repeats bring RAD51 from cytoplasm to the break sites in nucleus to initiate the repairing process. Missense variants in BRCA2 BRC repeats can interfere the interaction between BRCA2 and RAD51, impair double-strand break repair, cause genome instability and increase cancer risk. We characterized the missense VUS in BRCA2 BRC4 repeat, the primary site of BRCA2 interacting with RAD51. Based on the well-determined BRC4 structure, we applied MDS to measure the impact of BRC4 missense VUS on the stability of BRC4 structure by testing the equilibrium state, flexibility, compactness, hydrogen bonds and surface accessibility. Of the 46 missense VUS analyzed, we were able to differentiate them into 24 Deleterious and 22 Tolerated variants. Comparison between the MDS-based and other 24 existing computational methods for variant classification showed that the MDS-based approach is highly sensitive and specific for classifying missense VUS in cancer predisposition genes.